Stages of interaction of China and the Sverdlovsk region (Russia) under conditions of transformation in economic development models - Stepanov, Anatoly; Burnasov, Alexander; Ilyushkina, Maria; Kovalev, Yury; Kuzmin, Vadim (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2022)
The authors of the article observe the evolution of the economic cooperation between the Sverdlovsk region in Russia and the People’s Republic of China (PRC). In the research two major stages of the collaboration between two countries can be traced clearly: “the nomenklatura partnership” in the second half of the 20th century and “the market pragmatism” at the beginning of the 21st century. The aim of the paper is to investigate the ways of integration of the Sverdlovsk area as an old industrial region in the system of economic interaction with the People’s Republic of China, and define the reasons and factors for the dominant position of PRC in the foreign trade and economy of the Sverdlovsk region and the Urals, in general. The novelty of the study is to identify the particularity of the economic relations between one of the regions of the Russian Federation and the PRC under different conditions of the planned and market economic models using the demonstration of the exact examples. The research problem is to identify the risks and the drivers of the intensification of economic relations between the Sverdlovsk region (including its capital city of Yekaterinburg) and the PRC. Current research is carried out on the basis of a concrete-​​historical approach to the study of the stages of economic interaction between the USSR and Russia with the PRC using systemic and logical methods of analysis of the problems considered in it.